Pelatihan Pemanfaatan Media Sosial Untuk Promosi Budaya Guna Membantu Meningkatkan Pariwisata Desa Binaan Pulo Geulis-Bogor - Agustini, Vilya Dwi; Indriani, Indriani; Khotimah, Wininda Qusnul; Akbar, Doni Wahidul Akbar (Jurnal Pengabdian Kepada Masyarakat Kalam, 2024)
Tourism is one of the potentials that can move the economy and advance a region. When viewed in terms of geography, natural wealth and ethnic cultural wealth in the archipelago is very alarming if the tourism sector has not become a prima donna in improving the economy of its people. Some areas such as Bali, Lombok or Yogyakarta have been quite aggressive and good at maximizing the potential of their regions through various promotions either conventionally or using digital media. There is a tourist village in the Bogor area that already has a variety of potentials such as culinary and ethnic wealth but not many people know about it. Pulo geulis as a densely populated residential area located in Babakan Pasar Village. The service team is interested in seeing the potential of Pulo Geulis to increase promotion through social media which will ultimately help the local economy. By providing experts in the field of communication who are competent in providing internet-based media literacy is a solution to optimize the use of social media for promotional media. With good social media literacy, it will certainly make it easier for people to create a variety of promotional content for their area.